Vlogs for enhancing trainee teachers' motivational beliefs about school experience and teaching practice: They are on the factory floor for professional development - Debbağ, Murat; Fidan, Mustafa; Fidan, Mustafa; Debbağ, Murat (Routledge Journals, Taylor & Francis Ltd, 2022)
This study investigated the effectiveness of Vlogs on the motivational beliefs of trainee teachers in the practicum period. It also offers their perceptions of Vlogs for professional development. The participants were 54 trainee teachers from a university located in the north-west of Turkey. In this study, a pretest post-test quasi-experimental design with a control group was adopted to test the effects of using Vlogs on motivation. To collect qualitative data, semi-structured interviews were conducted in the experimental group. The results indicated that Vlogs had significantly positive effects on the sub-factors of motivation such as intrinsic goal orientation, control beliefs, self-efficacy, and task value. The experimental group had lower extrinsic goal orientation scores in comparison with the control group. The trainee teachers reported that Vlogs were a potential media not only for self-assessment, reflection, and peer learning but also for the development of techno-pedagogical skills in teacher education along with challenges of their use.
Keywords: Vlog; Blog Based Learning; Professional Development; Motivational Belief; Media In Teacher Education; Pedagogical Issues